Spatiotemporal pattern of thyroid cancer incidence in South Kerala: A population-based study - Preethi Sara George; Aleyamma Mathew; S Sruthi; Sreekumar Ananthakrishna Kurup; Jayasree Kattoor; T R Vinod (Wolters Kluwer Medknow Publications, 2023)
Background: Thyroid cancer (TC) is the most common endocrine cancer and has been increasing over the past decades worldwide. A notable finding is that Kerala's capital Thiruvananthapuram ranks the first among men and the second highest among women in the incidence of TC in India. Reasons for this increase have not been established. Objectives: Here, we investigated the spatiotemporal pattern of TC incidence in Thiruvananthapuram. Materials and Methods: TC incidence data (n = 1937) of Population Based Cancer Registry Thiruvananthapuram, Kerala, India, between 2012 and 2016, were analyzed for identifying geographical patterns by spatial methods, temporal methods for studying spatial variation in TC incidence, distribution of age, gender, and histology in lowland (coastal), midland, and highland. Results: Spatial clustering of TC incidence was identified consistently near the coastal region based on all geospatial analyses. 56.9%, 23.9%, and 19.2% of TC cases were observed in the coastal, midland, and highland areas, respectively. A significant clustered pattern of TC incidence was revealed by Moran's index I (0.49), high-high clusters by local Moran's, hotspot by Getis-Ord-Gi* (P < 0.05), point pattern analysis by nearest neighbor ratio and kernel density estimation. The relative risk of the significant cluster was obtained as 1.60 (95% confidence interval: 1.03-1.84) by SaTScan analysis. Conclusion: This study identified spatial variations in the pattern of TC cases with significant clusters near the coastal region of Thiruvananthapuram. This would help to pinpoint the high-risk geographical areas of TC and for more effective cancer control programs.